BISKUIT TERSUBTITUSI TEPUNG CANGKANG TELUR AYAM RAS DAN TEPUNG TERIGU SEBAGAI ALTERNATIF PANGAN SUMBER KALSIUM - Tambunan, Ellen Christ (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2025)
The purpose of this study was to determine the effect of chicken eggshell flour substitution as an alternative source of calcium on the characteristics and the best treatment for the characteristics of the resulting biscuits. The method used in this study was a completely randomized design with one factor. The factor was the concentration of chicken eggshell flour and wheat flour substitution, which consisted of four treatments, namely C1: 100% wheat flour concentration, C2 : : 75% wheat flour : 25% chicken eggshell flour concentration, C3 : 50% wheat flour : 50% chicken eggshell flour concentration, C4 : 25% wheat flour : 75% chicken eggshell flour concentration. The results showed that the substitution of chicken eggshell flour affected the moisture content, protein content, ash content, carbohydrate content, and fat content of the biscuits produced. However, it did not affect the calcium content and expansion of the biscuits. The best treatment for biscuits was treatment C3 (50% wheat flour and 50% chicken eggshell flour) with a calcium content of 1.81%, moisture content of 2.9%, ash content of 2.11%, protein content of 7.52%, fat content of 3.65%, and carbohydrate content of 83.8%.